Microbiome Associated with Slovak Raw Goat Milk, Trace Minerals, and Vitamin E Content - Andrea Lauková; Lenka Micenková; Ľubomíra Grešáková; Michaela Maďarová; Monika Pogány Simonová; Valentína Focková; Jana Ščerbová (International Journal of Food Science)
In Slovakia, goat milk production for direct consumption and cheese processing has attracted growing interest. However, there is a lack of information regarding the microbial consortium in Slovak raw goat milk analyzed by next-generation sequencing and trace elements and vitamin E as well. A randomly selected samples (G24-G50) of raw goat milk from different animals at farms in Slovakia were analyzed. The phylum Actinobacteria dominated (62.8%), followed by the phyla Firmicutes (20.5%), Proteobacteria (7.4%), and Bacteroidetes (6.4%). The family Microbacteriaceae was detected in the highest percentage (60.2%) followed by Staphylococcaceae, Bacteroidaceae, Streptococcaceae, Lactobacillaceae, Enterobacteriaceae, and others. Regarding the genera, the most prevalent was genus Curtobacterium (47.4%) followed by the genera such as Staphylococcus (8.3%) and Bifidobacterium (4%). The genera Streptococcus, Lactococcus, Enterococcus, Lactobacillus, and Lacticaseibacillus were evaluated in abundance percentage in range 1%-3.2%. The genus Veillonella reached abundance 3.2%. The genera Enterobacter, Pseudomonas (1.3% and 0.5%), and Bacteroides (6.4%) were evaluated in small percentage abundance too. Zinc was detected with the highest mean value (2.561±0.6823 mg/L) in raw goat milk, followed by iron (1.383±0.5087 mg/L). The mean value of copper and manganese was 0.1746±0.0463 mg/L and 0.051±0.0238 mg/L. The vitamin E reached the mean value 0.3783±0.1976 mg/L. This study is an original contribution showing microbial consortium in raw goat milk from Slovak farms. It also contributes to trace elements and vitamin E status in raw goat milk showing it as a nutritionally healthy food.